Study of the Life of the White Fly, Its Harms, and Biological Methods for Combating It - Abdalhadi, Danya Radhwan; Farhod, Ibrahim Saad; Hammad , Fatima Adel; Lafta, Ghadeer Falih (American Journal of Biology and Natural Sciences, 2025)
Whiteflies are a significant agricultural pest, causing extensive damage to crops through feeding and disease transmission. Despite various control strategies, effective and sustainable management remains a challenge due to their high reproductive rate and resistance to chemical pesticides. This study investigates the life cycle, ecological impact, and biological control methods of whiteflies using an integrated pest management approach. Through field observations and laboratory experiments, findings indicate that parasitoids and microbial agents are promising alternatives to chemical treatments, reducing whitefly populations while minimizing environmental harm. The results emphasize the necessity of adopting biological control measures to enhance sustainable agriculture and mitigate economic losses.